2022
DOI: 10.1002/alz.12734
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative loneliness and subsequent memory function and rate of decline among adults aged ≥50 in the United States, 1996 to 2016

Abstract: Introduction The study objective was to investigate the association between loneliness duration and memory function over a 20‐year period. Methods Data were from 9032 adults aged ≥50 in the Health and Retirement Study. Loneliness status (yes vs. no) was assessed biennially from 1996 to 2004 and its duration was categorized as never, 1 time point, 2 time points, and ≥3 time points. Episodic memory was assessed from 2004 to 2016 as a composite of immediate and delayed recall trials combined with proxy‐reported m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 66 publications
3
4
0
Order By: Relevance
“…Additionally, we identified linear trends in the association of the cumulative burden of social disconnection with incident CVD, all-cause mortality, and CVD mortality. Consistent with our findings, several previous cohort studies reported similar findings regarding dementia risk, where persistent loneliness was the most detrimental pattern for cognitive health [10,11,31]. These observations could indicate that social isolation and loneliness had a cumulative effect on cardiovascular and brain health.…”
Section: Associations Of Change In Social Isolation and Loneliness Wi...supporting
confidence: 92%
See 2 more Smart Citations
“…Additionally, we identified linear trends in the association of the cumulative burden of social disconnection with incident CVD, all-cause mortality, and CVD mortality. Consistent with our findings, several previous cohort studies reported similar findings regarding dementia risk, where persistent loneliness was the most detrimental pattern for cognitive health [10,11,31]. These observations could indicate that social isolation and loneliness had a cumulative effect on cardiovascular and brain health.…”
Section: Associations Of Change In Social Isolation and Loneliness Wi...supporting
confidence: 92%
“…Fifth, the study was unable to fully consider how changes in certain covariates over time might affect the results because these covariates were measured at different times. This aligns with the approach of existing studies that primarily focused on changes of exposure [10,11]. Additionally, these covariates have been proven to be stable over time [45], indicating that the changes in covariates are not likely to affect reliability of the current findings.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Two HRS studies explored loneliness using a one-item measure of loneliness from the CES-D. Donovan et al (2017) examined individuals 65 years and older and found that loneliness accelerated cognitive decline over a 12-year period even after accounting for relevant covariates including depressive symptoms. Similarly, Yu et al (2023) examined participants 50 years and older using the 1996–2016 HRS data and found that “cumulative loneliness” (increasing number of waves a participant acknowledged loneliness) was negatively associated with memory function.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous research has generally indicated that various aspects of poor social relationships, including social networks, loneliness, social support, and social engagement, are related to an increased risk of cognitive decline and impairment, the overall conclusion remains tentative. Some studies reported that feelings of loneliness, rather than objectively being alone or social disconnectedness, are associated with a higher risk of dementia among nondemented community-dwelling older adults ( Holwerda et al, 2014 ; Lara et al, 2019 ), whereas others found that objective measures of social disconnectedness, but not loneliness, predicted cognitive impairment ( Beller & Wagner, 2018 ; Jang et al, 2021 ; Yu et al, 2023 ). The inconsistent findings in previous studies may be attributed to variations in the approaches to defining and assessing social isolation, especially the objective aspects, as well as differences in cognitive outcome measures ( Evans et al, 2018 ).…”
Section: Two Aspects In Social Relationships: Social Disconnectedness...mentioning
confidence: 99%